Figure-of-merit for phase-change materials used in thermal management. (October 2016) - Shao, Lei; Raghavan, Arun; Kim, Gun-Ho; Emurian, Laurel; Rosen, Jeffrey; Papaefthymiou, Marios C.; Wenisch, Thomas F.; Martin, Milo M.K.; Pipe, Kevin P.
Highlights: A FOM for PCMs in thermal management is evaluated numerically and experimentally. Realistic boundary conditions leading to no explicit analytical solution are studied. The FOM is important in selecting PCMs, while sensible heat is a lesser design factor. Adding a PCM has little effect on an application's maximum steady-state duty cycle. A high- FOM PCM is experimentally shown to manage heat spikes in a smartphone. Abstract: In this work, we utilize a figure-of-merit ( FOM ) to compare the performance of various phase-change materials (PCMs) in managing short bursts of high-power heat flux, particularly those associated with microprocessors undergoing bursty operation on a time scale of approximately one second. We numerically investigate the FOM for applications that have realistic boundary conditions and lack analytical solutions. We also fabricate microprocessor proxies with integrated PCM compartments mounted in a smartphone package, and experimentally demonstrate the use of a high- FOM PCM to buffer short heat spikes as large as 11 W/cm 2 .